ChemInform Abstract: Zinc Chloride Catalyzed Stereoselective Construction of Spiropyrazolone Tetrahydroquinolines via Tandem [1, 5]‐Hydride Shift/Cyclization Sequence. Issue 10 (February 2016) - Zhao, Tuan; Zhang, Huanrui; Cui, Longchen; Qu, Jingping; Wang, Baomin
Abstract: Spiropyrazolone tetrahydroquinoline derivatives are directly synthesized through the title reaction in good to high yields and diastereoselectivities.